2019
DOI: 10.1167/tvst.8.3.28
|View full text |Cite
|
Sign up to set email alerts
|

Automated Measurement of the Foveal Avascular Zone in Swept-Source Optical Coherence Tomography Angiography Images

Abstract: The purpose of this study was to evaluate automated measurement of the foveal avascular zone (FAZ) area using the Kanno-Saitama macro (KSM) software in Image J with swept-source optical coherence tomography angiography (SS-OCTA) images. Methods: In this cross-sectional study, one photographer scanned the macular area (3 3 3 mm) of healthy volunteers twice on the same day, at the same time. The FAZ area was measured from the en face image of the superficial retinal layer by two masked examiners, using the KSM a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(57 citation statements)
references
References 52 publications
3
52
0
2
Order By: Relevance
“…another study reported that subjectively measured FAZ area did not differ between normal controls and patients with glaucoma. 9 We measured FAZ area objectively using an automated program 24 and confirmed an inverse association between FAZ area and degree of preoperative foveal sensitivity, suggesting that FAZ area enlargement in patients with POAG is associated with central VF loss. We demonstrated that perifoveal microcirculation was enhanced after glaucoma surgery.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…another study reported that subjectively measured FAZ area did not differ between normal controls and patients with glaucoma. 9 We measured FAZ area objectively using an automated program 24 and confirmed an inverse association between FAZ area and degree of preoperative foveal sensitivity, suggesting that FAZ area enlargement in patients with POAG is associated with central VF loss. We demonstrated that perifoveal microcirculation was enhanced after glaucoma surgery.…”
Section: Discussionmentioning
confidence: 57%
“…The qualitative protocol has been described. 23 24 In brief, two blinded investigators (YY and HI) reviewed all images independently. Poor-quality scans were excluded if any of the following criteria were met: (1) poor-clarity images, (2) weak local signal caused by artefacts such as visual floaters, (3) residual motion artefacts visible as irregular vessel patterns or disc boundaries on enface angiography and (4) images with an off-centre fovea.…”
Section: Qualitative Protocolmentioning
confidence: 99%
“…The second work on which our method relies is a study by Ishi et al (22), where the authors proposed and evaluated a macro-based automated analysis method called Kanno-Saitama Macro (KSM) to measure the FAZ area using ImageJ software. The study concluded that this automated method was comparable to manual measurement, saving time and being less user-dependent.…”
Section: Image Processingmentioning
confidence: 99%
“…Moreover, the mKSM is tolerant to images that are not perfectly centred or with artefacts, while the original Kanno-Saitama macro (22) only used images perfectly centred and without artefacts. This tolerance makes mKSM usable for images from the real world that could be acquired in a regular clinic.…”
Section: Study Limitationsmentioning
confidence: 99%
“…19 Some automated customized methods have been reported for other OCTA systems. Ishii et al 20 reported that the Kanno-Saitama macro (KSM) produced reliable results in the Zeiss PLEX Elite 9000; however, the reliability of the macro in the Cirrus HD-OCT 5000 has not yet been determined, and other image processing methods should be explored for more reliable measurements in the Cirrus HD-OCT 5000. In this study, we utilized the Level Sets macro (LSM), a plugin for ImageJ software (National Institutes of Health, Bethesda, MD) to measure the FAZ, and we compared the results with measurements by the Cirrus inbuilt algorithm and the KSM.…”
Section: Introductionmentioning
confidence: 99%